Polyfluorinated Chemicals and Transformation Products - Knepper, Thomas P.; Lange, Frank T. (The Handbook of Environmental Chemistry,, 2012)
Due to their unparalleled effectiveness and efficiency, polyfluorinated chemicals (PFC) have become essential in numerous technical applications. However, many PFCs brought to market show limited biodegradability, and their environmental persistence combined with toxic and bioaccumulative potential have become a matter of concern in some instances. This volume highlights the synthesis of PFCs, focusing on substances with improved application and environmental properties, which are a challenge for synthetic chemists. Further, modern mass spectrometric techniques for the detection and identification of biotransformation products of PFCs are described. The sorption and leaching behavior of PFC in soil is also addressed in order to predict their fate in the environment. Several contributions discuss the monitoring of PFCs in European surface, ground and drinking waters, treatment options for PFC removal from drinking water, occurrence in food, and the human biomonitoring of PFCs.